Lung Cancer Presenting as Acrometastasis to the Finger: A Case Report - Lawrence Stephen Long; Leslea Brickner; Lisa Helfend; Tony Wong; Derek Kubota (Case Reports in Medicine)
Lung cancer is the commonest cause of acrometastatic disease to the fingers. Here we describe a case of occult lung cancer presenting as unrelenting finger pain and swelling from a metastatic phalangeal fracture. The patient's management was largely palliative and he died soon after discovery of the primary tumor. Digital acrometastatic disease rarely becomes symptomatic before the primary lung cancer is diagnosed and, as observed in this case, carries a very poor prognosis. Clinicians should be cognizant of the strong association between digital acrometastases and bronchogenic carcinoma and vigilant in screening high-risk patients with importunate finger symptoms.